ANALISIS PERFORMA ALAT DISTILASI SURYA DENGAN VARIASI KETEBALAN KACA PENUTUP - Ida Bagus Alit; Made Wirawan; Irham Zulkarnain (Energy, Materials and Product Design, 2026)
The availability of clean water has become a global challenge due to the dominance of seawater on Earth and the limited amount of usable freshwater. One potential solution is solar distillation, which utilizes solar energy as a renewable energy source. This study aims to analyze the effect of glass cover thickness on the performance of the solar distillation system, including temperature distribution, water productivity, and system efficiency. The glass thicknesses used in this study were 3 mm, 5 mm, and 8 mm. The results showed that glass thickness significantly affected system performance. 3 mm glass produced the highest productivity of 1073.33 ml/day with an efficiency of approximately 39%, followed by 5 mm and 8 mm glass. Increasing glass thickness reduced temperature, evaporation rate, and distillation yield due to higher thermal resistance and lower solar radiation transmission. Therefore, the optimal glass thickness is 3–5 mm to achieve maximum system performance.